Análisis financiero a la cooperativa de transportes Loja, períodos 2019-2020 - Pineda Criollo, Josselyn Anahí (2022)
The Curriculum Integration Work titled: COOPERATIVE OF TRANSPORTS LOJA, PERIODS 2019-2020; was carried out to establish and evaluate the economic and financial position of the cooperative, through the application of techniques and procedures of the financial analysis such as the variations found in the vertical and horizontal analysis; In addition, the levels of liquidity, activity, indebtedness, and profitability were determined through the application of financial indicators, and a financial report was prepared with the results obtained from the financial analysis to finally reach conclusions and recommendations to optimize the deficiencies found, contributing to the progress and therefore the development of the cooperative. The vertical analysis was carried out, calculating the proportional weight and knowing that the financial structure for the year 2019 with total assets of $ 12,090,529.57 the same that are financed by the liabilities in a percentage of 53.88 % and 46.12 % corresponds to the patrimony; to the year 2020, the total assets are $ 12,972,998. 21 which are financed by liabilities in a proportion of 61.96 % and 38.04 % belongs to equity, which means that in both periods the assets are financed with debt. The horizontal analysis was also applied to the financial statements for the period 2019-2020 to determine the variations presented by each of the accounts that make up the financial statements, where the assets had a growth of 7.30 % which in monetary value is $ 882,468.64; for its liabilities, these rose by 23.39 %, this corresponds to a value of $ 1,523,633.43 for the last year. Likewise, its equity has suffered a significant decrease of -11.50 %, with a value of $ -641,163, registering a loss in both years. The third specific objective was: to apply financial indicators to the financial statements demonstrating the level of liquidity, activity, indebtedness, and profitability of the company, resulting in a liquidity level of 1 for the year 2020, $ 1.22 inferring that the cooperative has sufficient liquidity to pay off its short-term debts; within the activity indicators they presented an inventory permanence of 53 days, the collection period of accounts receivable is 159 days, and accounts payable 183 days; about the indebtedness indicators, the index was $ 0.62, i.e., its indebtedness is moderate because the debts they have do not affect the cooperative and concerning equity, the creditors have a minimum intervention in the cooperative. To fulfill the last objective set for the research: to prepare a report product of the results of the financial analysis containing conclusions and recommendations to help managers in their management and to make the best decisions for the benefit of such an important transport cooperative, which is addressed to the manager of the cooperative, which includes a summary of the financial analysis of the financial statements for the periods 2019 and 2020 to be taken into consideration, conclusions and recommendations that are aimed at providing solutions to the shortcomings found